'Will I learn what I want to learn?' Usable representations, 'students' and OECD assessment production - Shahjahan, Riyad A.; Morgan, Clara; Nguyen, David J. (Discourse (Abingdon, England), 2015)
Amid growing debates around international assessment tools in educational policy, few have critically examined how students themselves are cast in policy tool production processes and discourse. Drawing on Stuart Hall's concept of representation, we show how higher education (HE) 'students' are constructed, fixed and normalized by the Organisation for Economic Co-operation and Development's (OECD) Assessment of Higher Education Learning Outcomes (AHELO) initiative. Based on an analysis of AHELO texts, we argue that the OECD, during the early stages of test production, fixes and circulates the meaning of 'students' as represented objects. We identify and analyze two distinct representational practices at work in AHELO texts: classifying and organizing, and marking. We posit that by fixing images of the student as an object of learning and as a consumer-investor subject, the OECD creates 'usable' representations of 'students' to claim jurisdiction over teaching and learning in HE and to justify intervention through standardized testing.